(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the surgical outcomes of intraocular lens (IOL) fixation using the Yamane technique for the treatment of traumatic crystalline lens injury in children. Subjects and Methods: A descriptive, prospective, uncontrolled study was conducted on 30 eyes of 30 pediatric patients (≤15 years) who underwent sutureless IOL fixation with the Yamane technique at the Vietnam National Eye Hospital from January 2020 to July 2025. Data were collected preoperatively and at 1 week, 1 month, and 3 months postoperatively, including baseline patient characteristics, lens status, surgical complications, and overall surgical outcomes. Results: At 3 months after surgery, 86.7% of eyes achieved good outcomes and 13.3% achieved fair outcomes. Mean best-corrected visual acuity (BCVA) improved significantly, with logMAR BCVA increasing from 1.52 preoperatively to 0.63 at 3 months (p<0.001). The complication rate was low: mild IOL decentration occurred in 3.3% of eyes, and ocular hypertension developed in 10.0% of eyes within 3 months postoperatively. Conclusion: Yamane sutureless IOL fixation appears to be an effective and initially safe surgical option for managing traumatic lens injury in children, providing good visual recovery with a low rate of complications during the 3-month follow-up period.